Preaching In Marginal Spaces: Audience Reception Of Gus Miftah's Da'wah Through Stuart Hall's Encoding-Decoding Approach - Luluk Ilma Inun; Nur Rovida Femila Sari; Luluk Fikri Zuhriyah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The phenomenon of preaching in non-conventional spaces such as nightclubs has drawn attention because it presents a form of religious message delivery that adapts to the socio-cultural context of marginalized audiences. Gus Miftah, as a contemporary preacher, utilizes these spaces, both directly and through digital media, to convey inclusive and communicative preaching. This study aims to analyze the process of encoding da'wah messages by Gus Miftah in the video “LC Karaoke Bertanya, Gus Miftah Ngaji di Boshe” and the audience’s reception (decoding) through comments on YouTube. Using a descriptive qualitative approach and Stuart Hall’s encoding-decoding theory, data were collected through video documentation and purposive observation of comments. The results show that the da'wah messages are constructed contextually and humanistically, with a relaxed, humorous style and language familiar to nightlife workers. The analysis reveals three audience reception positions: the majority fully accept the message, a small portion critically engages with the context, and others reject the preaching method as incompatible with traditional values. These findings indicate that the audience’s cultural, social, and religious backgrounds strongly influence the response to da'wah. This study enriches the discourse on digital da'wah and emphasizes the importance of understanding the audience as active subjects in communication. Conclusion: A contextual preaching approach effectively penetrates non-conventional spaces and is widely accepted, despite resistance from conservative and critical audiences.